2014
DOI: 10.4293/108680813x13753907291918
|View full text |Cite
|
Sign up to set email alerts
|

Operative Time and Outcome of Enhanced Recovery After Surgery After Laparoscopic Colorectal Surgery

Abstract: Background and Objectives:Combining laparoscopy and enhanced recovery provides benefit to short-term outcomes after colorectal surgery. Advances in training and techniques have allowed surgeons to operate on cases that are technically challenging and associated with prolonged operative time. Laparoscopic techniques improve the outcome of enhanced recovery after colorectal surgery; however, there are no specifications on the effect of prolonged operations on the outcome. The objective was to elucidate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
(49 reference statements)
4
21
0
3
Order By: Relevance
“…Total gastrectomy is likely to be more complicated than distal gastrectomy because it is difficult to dissect lymph nodes along the splenic artery and perform an esophagojejunostomy. It is found that a prolonged operating time and major operative blood loss are associated with poorer outcomes, which may contribute to delayed recovery even in the presence of an established enhanced recovery program [31]. Carbohydrate loading is an important item in the ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Total gastrectomy is likely to be more complicated than distal gastrectomy because it is difficult to dissect lymph nodes along the splenic artery and perform an esophagojejunostomy. It is found that a prolonged operating time and major operative blood loss are associated with poorer outcomes, which may contribute to delayed recovery even in the presence of an established enhanced recovery program [31]. Carbohydrate loading is an important item in the ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this surgery-specific effect reflects the fact that laparoscopic resection, although it usually takes longer than open resection, induces less trauma and stress in the patient. In addition, recovery-enhancing methods are easier to apply after laparoscopic resection because of less trauma3940. Thus the clinical benefit of chewing gum may have been too weak to be observed in the entire study population or in the subgroup of those who underwent the laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In procedures where a skin incision is not made (such as endoscopic examination), the time taken for the procedure to be performed (defined as time from insertion to withdrawal of the endoscope for endoscopic examinations) was used. This measure was chosen because it is strongly correlated with surgeon performance, the focus of the study, and previous studies have shown a relationship between this variable and clinical outcomes across a range of operations. In addition, duration of operation is recorded routinely in Spire Healthcare hospitals, and is not affected by loss of patients to follow‐up, unlike other measures of clinical outcome such as hospital death.…”
Section: Methodsmentioning
confidence: 99%